Reading and reasoning: a problem solving approach (1995)
Reading and reasoning deals with one particular aspect of the teaching of English as a foreign language: english for academic purposes (EAP). The aim of this material is to help students of English as a Second Language develop their reading skills so that they can become good readers in English. Most of these skills are already used in their first language such as skimming, scanning, predicting or reacting in a critical way. The material has been designed mainly for National University students in order to prepare them to read texts in English; however, it might also be used by other learners who share the same needs and interests. it can be used by teachers as course materia!, supplementary materia!, or by students as self-access material. This manual mainly focuses on a set of tasks that students develop by applying their own learning strategies. There is a section oriented towards Problem Solving that consists of creating a problem, a case study or a hypothetical situation based on ¡deas taken from the text of each unit. This approach allows students to créate opportunities to use their own knowledge and experience of the world, to explore their potential, to evalúate and raise issues in such a way that finally students are able to propose solutions to it. / Contenido. Preliminares; Capítulo 1 - Ecrainish settlers in the neowo; Capítulo 2 - Brain as a renewable resource; Capítulo 3 – 4 - Mathematicians in the doldrums – Teaching vs. Research; Capítulo 5 - Profile: Rita Levi-Montalcini finding the good in the bad; Capítulo 6 - Snobs; Capítulo 7 - Adding up the Under-Skilled; Anexos.